2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591427
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of individual prosthesis size for valve-sparing aortic root reconstruction based on geometric features

Abstract: Valve-sparing aortic root reconstruction is an up- and-coming approach for patients suffering from aortic valve insufficiencies which promises to significantly reduce complications. However, the success of the treatment strongly depends on the challenging task of choosing the correct size of the prosthesis, for which, up to now, surgeons solely have to rely on their experience. Here, we present a novel machine learning based approach, which might make it possible to predict the size of the prosthesis from pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…One possibility to overcome this problem could be an additional estimation step predicting the healthy geometry based on the obtained one. A similar approach was already tested in a comparable cardiovascular problem [6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility to overcome this problem could be an additional estimation step predicting the healthy geometry based on the obtained one. A similar approach was already tested in a comparable cardiovascular problem [6].…”
Section: Resultsmentioning
confidence: 99%
“…2 (c)). Previous studies have shown that this simple geometric description allows for a reasonable representation of the individual geometry [6]. Based on these landmarks, different geometric key features were extracted, namely the commissure distances K 1 , K 2 and K 3 as well as the leaflets' free edge lengths S 1 , S 2 and S 3 (see Fig.…”
Section: Curved Shape Acquisitionmentioning
confidence: 99%
“…To evaluate our method, we tested it on an ex-vivo porcine data set. The data set was published in [3] and consists of 3D ultrasound images of 24 isolated aortic roots in the closed state under physiologically realistic pressure conditions. During the collection of the data set, at first, images of the natural aortic roots were taken.…”
Section: Data Setmentioning
confidence: 99%
“…In this first approach, we extracted one 2D slice image from each volume in which the commissure plane, i.e. the slice image were all three commissure points are visible, is shown [3].…”
Section: Data Setmentioning
confidence: 99%
See 1 more Smart Citation